Eurilia (European Initiative in Library & Information in Aerospace) : - Blagden, J F (Cranfield University, 1994)
The study reported here is part of the Eurilia (European Initiative in Library and Information in Aerospace) project, the aim of which is to enhance the Libraries’ R&D and education process which underpins the aerospace sector by establishing a new service based on a standardised pan-European system for information access, retrieval, image browsing and document delivery. This will in turn extend the access and availability of major aerospace collections. The partners in this project are: University of Limerick, Delft University of Technology, Digital Equipment Corporation, Sup’Aero, ENSAE - Ecole National Superieure de 1’Aeronautique et de l’Espace, Instituto Nacional de Tecnica Aeroespacial, Cranfield University The work for this study was largely undertaken by Cranfield University, but all partners have provided useful input and comments particularly in terms of the interviews conducted in each Eurilia country. The University would also wish to thank the EC European Action Programme for Libraries for the support for Eurilia in general and this phase of the project in particular. This report was originally submitted to the EC as Eurilia (European Initiative in Library and Information in Aerospace), Pre- project Audit, Project LIB-EURILIA/3-2083 funded by the European Action Programme for L